2011
DOI: 10.1002/mnfr.201000419
|View full text |Cite
|
Sign up to set email alerts
|

Lunasin induces apoptosis and modifies the expression of genes associated with extracellular matrix and cell adhesion in human metastatic colon cancer cells

Abstract: Lunasin can be used in cases where resistance to chemotherapy developed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
81
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(97 citation statements)
references
References 48 publications
3
81
2
Order By: Relevance
“…Lunasin (LUN) is a 43-amino acid peptide component of post-translationally processed 2S albumin, initially identified in soybeans (Galvez and de Lumen 1999) and also present in barley, wheat and other seeds (Jeong et al 2007(Jeong et al , 2010Silva-Sanchez et al 2008). The anti-carcinogenic properties of LUN have been demonstrated in rodent models of skin (Galvez et al 2001) and breast (Hsieh et al 2010a, b) cancers and in colon and breast cancer cell lines Hsieh et al 2010c;Dia and Gonzalez de Mejia 2011). Thus far, it is not known how LUN measures up to GEN as a dietary factor with anti-cancer preventative activities.…”
Section: Introductionmentioning
confidence: 99%
“…Lunasin (LUN) is a 43-amino acid peptide component of post-translationally processed 2S albumin, initially identified in soybeans (Galvez and de Lumen 1999) and also present in barley, wheat and other seeds (Jeong et al 2007(Jeong et al , 2010Silva-Sanchez et al 2008). The anti-carcinogenic properties of LUN have been demonstrated in rodent models of skin (Galvez et al 2001) and breast (Hsieh et al 2010a, b) cancers and in colon and breast cancer cell lines Hsieh et al 2010c;Dia and Gonzalez de Mejia 2011). Thus far, it is not known how LUN measures up to GEN as a dietary factor with anti-cancer preventative activities.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that lunasin causes cytotoxicity in four different human colon cancer cell lines, KM12L4, RKO, HCT-116, and HT-29 cell, with IC50 values of 13.0 µM, 21.6 µM, 26.3 µM and 61.7 µM, respectively [59]. These values suggest that lunasin is most potent killing the highly metastatic KM12L4 colon cancer cells than any other colon cell lines used in this study.…”
Section: Lunasin Against Colon Cancer In Vitromentioning
confidence: 61%
“…Studies on mechanism of action of this peptide have revealed that lunasin causes arrest of cell cycle in G2/M phase and induction of the mitochondrial pathway of apoptosis. The cell cycle arrest was attributed with concomitant increase in the expression of the p21 protein in HT-29 colon cancer cells, while both p21 and p27 protein expressions were up-regulated by lunasin treatment in KM12L4 colon cancer cells [59,61]. Moreover, treatment with lunasin decreased the ratio of Bcl-2:Bax by up-regulating the expression of the pro-apoptotic Bax and down-regulating the expression of the anti-apoptotic Bcl-2, also increasing the activity of caspase-3 [61].…”
Section: Lunasin Against Colon Cancer In Vitromentioning
confidence: 92%
See 1 more Smart Citation
“…Previous studies have acknowledged that lunasin reduces cyclin-dependent kinase (CDK) levels, and may accommodate aspirin-induced apoptosis in breast cancer models [22,23]. Additionally, lunasin was reported to induce apoptosis and alter expression of matrix adhesion proteins in metastatic colon cancer [24]. Lunasin was recently shown to suppress FAK/ERK/NF-κB signaling in human colon cancer as well as potentiate the antiproliferative and antimetastatic effects of oxaliplatin [25].…”
Section: Lunasin As An Anticancer Agentmentioning
confidence: 99%